Discriminating mesozooplankton communities in Bushehr marine coastal ecosystems- Persian Gulf - Mokhayer, Z; Mousavi Nadushan, R; Rabbaniha, M; Fatemi, M R; Jamili, Sh (Iranian journal of fisheries sciences, 2017)
Coastal ecosystems of Bushehr are shallow environments subject to human impacts, including shrimp aquaculture and urban expansion activities. A spatial-temporal study was conducted in order to assess the actual ecological status of the creeks, estuary and marine sites on the basis of their taxonomic composition and density of mesozooplankton. Zooplankton species distribution and abundance data at 6 sampling sites during June 2015 - March 2016 revealed 24 taxa represented by 5 divergent groups. During the study period, high salinities (around 35-47 PSU) were recorded, characterizing all systems as a coastal-marine ecosystem, rather than true estuarine. The mesozooplankton assemblage was characterized by the dominant marine Copepod, Labidocera sp., zoeas of coastal/marine crab, Ilyoplax frater, marine copepod Acartia fossae and a marine pelagic tunicate, Oikopleura dioica. Copepods were the main dominant group and Labidocera sp. the most abundant species, with high abundances in winter, whereas high abundances of the Ilyoplax frater were noticed in summer. Based on SIMPER analyses, highest dissimilarity was observed between Ramleh and Lashkary and discriminating taxa for all sites were Labidocera sp followed by Ilyoplax frater contributing to more than 68% of the total average dissimilarities for all locations. The multivariate BIO–ENV procedure indicated that Labidocera sp. followed by Acartia fossae strongly correlated to the variability of depth, transparency and salinity. Finally the results showed that temporal and spatial variation in the mesozooplankton community is consistent with the dynamic character of the habitat characterized as a typical coastal marine system (with low average depths, transparency and high salinity).